IDENTITAS ORANG MELAYU DI HULU SUNGAI SAMBAS - Yusriadi, Yusriadi (Khatulistiwa, 2015)
This writing is grounded from the willing to look at the form and constructed material of Malay identity in the Sambas river headwaters. It is derived from the qualitative descriptive research formerly done by the writer. Furthermore, the data is collected in Sepandak area, one of Malay villages in Sambas river headwaters, that is far from the main area of Sambas cultural. This village, moreover, is chosen due to its position that lies in the end of Sambas river. The village’s leaders, social leaders, religion leaders, and housewives are interviewed and observed to gain the information and their point of view about Malay identity. As a result, this research concludes that the Malay in the Sambas river headwaters has similar identity to Sambas people. The charactersitics of Malay people there are also same as other communities dwelling around them that people can distinguish the differences among them. The materials used as the differential mark are languages and names, houses and the utensils, the marriage tradition, the official dress, and the traditional arts. To wrap up, the research explains Islam as one of the constructed identities among Malay people in Sepandak shown by the built mosque, house accessories, and the Islamic arts.